Pediatric Inflammatory Bowel Disease - Mamula, Petar; Markowitz, Jonathan E.; Baldassano, Robert N. (Springer US : Imprint: Springer, 2008)
Pediatric Inflammatory Bowel Diseases (IBD) are the most common and most significant chronic disorders in Pediatric Gastroenterology. The onset of Crohn disease and ulcerative colitis in the first two decades of life presents a number of diagnostic and therapeutic challenges that are unique to pediatric patients. Although the studies available for pediatric diagnosis have improved dramatically in the past three decades, the improvement in technology alone cannot account for the increased frequency of IBD recognized in early childhood. While therapy for older patients has improved dramatically with the use of immunomodulators and the development of exciting biologic strategies, rarely if ever have comprehensive studies of the pharmacokinetics, safety and efficacy of any of the IBD medications been performed in pediatric patients. A number of excellent medications are not available in liquid preparations that can be swallowed by children, and others, such as timed-release formulations, are developed for delivery to an adult gastrointestinal tract. It is unfortunate that the care we provide to children is often an extrapolation of what is known about and available for adults with IBD. Pediatric patients with IBD face a number of unique challenges. The onset of disease before puberty can be devastating. Growth failure is a particularly difficult problem with potentially permanent consequences. Much of the pediatric specific research has focused on the role of nutritional therapy to treat growth failure and induce remission.